2007
DOI: 10.1038/sj.jp.7211751
|View full text |Cite
|
Sign up to set email alerts
|

Association between early postnatal weight loss and death or BPD in small and appropriate for gestational age extremely low-birth-weight infants

Abstract: Objective: To examine the association between weight loss during the first 10 days of life and the incidence of death or bronchopulmonary dysplasia (BPD) in small for gestational age (SGA) and appropriate for gestational age (AGA) extremely low-birth-weight infants.Design/Methods: This is a retrospective analysis of a cohort of ELBW (birth weight <1000 g) infants from the NICHD Neonatal Research Network's database. The cohort consisted of 9461 ELBW infants with gestational age of 24-29 weeks, admitted to Netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 20 publications
(24 reference statements)
0
39
0
Order By: Relevance
“…4,7,11,12 However, other observational studies have shown no difference in the early fluid regimens (first 4 to 14 days) of infants who develop BPD 27 or PDA 16,17 compared to those who do not.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…4,7,11,12 However, other observational studies have shown no difference in the early fluid regimens (first 4 to 14 days) of infants who develop BPD 27 or PDA 16,17 compared to those who do not.…”
Section: Discussionmentioning
confidence: 98%
“…Although over-hydration has been implicated in the development of both BPD and PDA, [1][2][3][4][5][6][7][8][9][10][11][12] it is not clear from prior studies whether complications arising from excessive hydration are due to fluid therapy itself, to an increase in total body water resulting from decreased renal losses or an increase in extracellular water volume due to third spacing. 6 To address this question, regression models were run that included weight change in grams per kg of body weight per day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid increase in enteral feeding is a known risk factor for NEC (Berseth et al 2003). In ELBW infants, high fluid intake associated with less weight loss during the first 10 days of life is associated with an increased risk of death and BPD (Oh et al 2005, Wadhawan et al 2007). In addition excessive catch up growth may result in adverse cardiovascular outcomes later in life.…”
Section: A Note Of Caution Regarding the Use Of Intra Uterine Growth mentioning
confidence: 99%